Piano trio in G Major, op. 1, no. 2, published by Simrock - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; N. Simrock; Bonn, 2024)
Early edition of the Piano Trio in G Major, op. 1, no. 2, published by Simrock, later issue with variant title page and plate number 37, lacking printed price.